“Sirin is not inferior to Leonov”: Burrows’s Delta for stylometric analysis of Russian novels of the interwar period - F. N. Dviniatin; B. V. Kovalev (Шаги)
The article analyzes the stylistic features of Nabokov’s Russian-language novels in the context of Russian interwar prose. The main method is Burrows’s Delta — one of the most reliable stylometric tools that allows comparing texts with each other based on the distribution of the most frequent function words. In addition, SVM and KNN methods are also used to classify texts. The study has two objectives: 1) to carry out a primary clustering of the styles of leading Russian prose writers of a certain era, and also, through the use of modern algorithms, to determine the place among them of the style of Nabokov (Sirin); 2) to test these algorithms for their ability to informatively and adequately solve the tasks of stylistic distribution and for the consistency of the results. It turns out that stylistically close to Nabokov’s novels are the texts of Leonov, Gazdanov and Grin. A particularly clear similarity is found between Nabokov’s late novels, Leonov’s Skutarevsky and Gazdanov’s An Evening with Claire. Nabokov’s eight Russian-language novels are divided into two groups. The first consists of Mashenka, The Defense, King, Queen, Knave, Glory, Laughter in the Dark. The second is made up of the novels of the 1930s: Despair, Invitation to a Beheading, The Gift.